2017
DOI: 10.1002/cptc.201600038
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Carbon Quantum Dots for Sensitized Solar Cells

Abstract: Carbon quantum dots (CQDs) have attracted tremendous interest owing to their application in bioimaging, sensors, medicine and catalysis. Herein, CQDs were prepared from several carbon sources as sensitizers for solar cells. Of the CQDs prepared, bee‐pollen‐based CQDs (B‐CQDs) achieved the highest power conversion efficiency of 0.11 % under one sun illumination (AM 1.5).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 35 publications
1
32
0
Order By: Relevance
“…Guo et al. developed CDs from bee pollen, citric acid, and glucose through hydrothermal reactions . Because of hole transfer and the small size of the pollen‐based CDs, the efficiency of the sensitized solar cell reached 0.11 %.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Guo et al. developed CDs from bee pollen, citric acid, and glucose through hydrothermal reactions . Because of hole transfer and the small size of the pollen‐based CDs, the efficiency of the sensitized solar cell reached 0.11 %.…”
Section: Applicationsmentioning
confidence: 99%
“…Guo et al developed CDs from bee pollen, citric acid, and glucose through hydrothermalr eactions. [72] Because of hole transfer and the small size of the pollen-basedC Ds,t he efficiency of the sensitized solar cell reached 0.11%.I na ddition, Mirtchev et al reported the charge transport and injection properties of CDs (from gbutyrolactone) in TiO 2 solar cells, whichs howed 0.13 %p ower conversion efficiency. [5a] In solar cell systems, CDs limit charge recombination and enhance charge transport, thereby enhancing these properties, especially after heteroatom doping.…”
Section: Solar Cellsmentioning
confidence: 99%
“…As an alternative of fossil fuel-based energy sources, numerous nanoscale materials have been used in the fabrication of highly efficient, green, low cost and scalable photovoltaic devices, especially solar cells (SCs). 2,29,[147][148][149][150][151][152][153][154][155][156] To date, most of the SCs (such as organic SCs, silicon based SCs, and dye/QD-sensitized SCs (DSSCs/QDSSCs)) are based on the use of toxic nanomaterials, with a lack of scalability, renewability and maximum power conversion efficiency. 2,29,[147][148][149][150][151][152][153][154][155][156] In this regard, the ecofriendly, inexpensive biomolecule-based C-QDs and G-QDs, with the scope of scalability and renewability and alluring optical features, have started to gain interest due to their different photovoltaic activities, such as sensitizers and photoabsorption agents (due to their absorption tail in the visible zone), charge carrier sources, and bridges and funnels (due to their large p-electron network (sp 2 core) and electron donating and accepting capability).…”
Section: Solar Cells and Energy Conversionmentioning
confidence: 99%
“…2,29,[147][148][149][150][151][152][153][154][155][156] To date, most of the SCs (such as organic SCs, silicon based SCs, and dye/QD-sensitized SCs (DSSCs/QDSSCs)) are based on the use of toxic nanomaterials, with a lack of scalability, renewability and maximum power conversion efficiency. 2,29,[147][148][149][150][151][152][153][154][155][156] In this regard, the ecofriendly, inexpensive biomolecule-based C-QDs and G-QDs, with the scope of scalability and renewability and alluring optical features, have started to gain interest due to their different photovoltaic activities, such as sensitizers and photoabsorption agents (due to their absorption tail in the visible zone), charge carrier sources, and bridges and funnels (due to their large p-electron network (sp 2 core) and electron donating and accepting capability). 2,29,[147][148][149][150][151][152][153][154][155][156] Importantly, the use of man-made material-based C-QDs and G-QDs has been displayed to have applicability in developing heterojunction solar cells devices (ZnO QDs/G-QDs and CDs/Si: with enhanced absorption and suppressed recombination and thus higher efficiency compared to their parent components), open circuit voltage increment in devices (depending on the quantum size effect of the G-QDs), solution-processed organic/metal oxide and dyesensitized solar cells (such as combination of poly(3hexylthiophene) (P3HT) and GQDs, and TiO 2 with G-QDs and...…”
Section: Solar Cells and Energy Conversionmentioning
confidence: 99%
“…Although the catalytic chemical vapor deposition can be used to fabricate 1D and 2D carbon materials, the required devices and catalytic nanoparticles are essential, where iron is used to constitute the CNFs and copper is employed to assemble 2D graphene . Certainly, the whole dimensions of carbon nanostructures can also be obtained by the biomasses, but the raw materials are restricted. The bee pollen, cellulose, corn, and peat mosses are transformed into 0D CQDs, 1D CNFs, 2D graphene, as well as 3D macroscopic carbon frameworks, respectively.…”
Section: Introductionmentioning
confidence: 99%